The Effect Of Articulation Type Cooperative Learning Model Assisted By Digital Media On The Speaking Skills Of Grade V Students - Anwar, Nur Azmi; Kaddas, Badruddin; Selvi, Nurhayati (Program Studi Pendidikan Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2025)
The problem in this study is the low speaking skills of students where students still have difficulty pronouncing sentences clearly and also the low desire of students to express ideas in front of the class.This study aims to determine: 1) the application of cooperative learning model of articulation type assisted by digital media to fifth grade students of SD Inpres Kaluku Bodoa, 2) speaking skills of fifth grade students with cooperative learning model of articulation type assisted by digital media at SD Inpres Kaluku Bodoa, 3) differences before and after the application of cooperative learning model of articulation type assisted by digital media on speaking skills of fifth grade students of SD Inpres Kaluku Bodoa. This type of research is experimental research with a one group pretest-posttest design with a sample size of 19 students using interview instruments, observation sheets, oral tests and documentation. In this study using descriptive statistical analysis and inferential analysis with the help of SPSS version 26.The results of this study indicate that the Effect of Articulation Type Cooperative Learning Model Assisted by Digital Media on Speaking Skills of Class V Students of SD Inpres Kaluku Bodoa through several stages of material delivery, forming groups, delivering material that has been delivered by the teacher, students listening and making small notes, students delivering interview results in class V SD Inpres Kaluku Bodoa has been carried out well and effectively. students' speaking skills can be seen from the comparison between pretest and posttest. The average value of the pretest obtained is 64.21, the average value is in the interval 55-69 which is included in the low category. While the average value of the posttest is obtained by 87.57 which is in the interval 85-100 which means it is in the very high category. The results of the study were obtained using the Mann whitney test where the asymp.sig (2-tailed) value was ,000 which can be said that Ha is accepted and HO is rejected because 000 <0.05.